2023
DOI: 10.3390/su15021175
|View full text |Cite
|
Sign up to set email alerts
|

Undrained Shear Properties of Shallow Clayey-Silty Sediments in the Shenhu Area of South China Sea

Abstract: Suction piles are used to ensure wellhead stability during natural gas hydrate production in the Shenhu area of the South China Sea (SCS). Undrained shear properties of clayey-silty sediments play a critical role in the stability analysis of suction piles. However, it has not been fully studied. This study conducts a series of undrained triaxial shear tests on shallow clayey-silty sediments in the Shenhu area of SCS, and stress–strain curves under different overconsolidation ratio (OCR) conditions are obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
1
0
0
Order By: Relevance
“…In contrast, th maximum dry unit weight and optimal moisture content correspond to the fitted curve The dry density and the water content curves are shown in Figure 4, which shows that the dry density increases with moisture content and then decreases. In contrast, the maximum dry unit weight and optimal moisture content correspond to the fitted curve's top, consistent with the dry density of fine-grained soil [27,28]. Wang et al [29,30] found that the dry density of gravelly calcareous sand increased with increasing water content when the water content was greater than 8%.…”
Section: Maximum Dry Density Experiments Of Round Gravel Soilsupporting
confidence: 64%
“…In contrast, th maximum dry unit weight and optimal moisture content correspond to the fitted curve The dry density and the water content curves are shown in Figure 4, which shows that the dry density increases with moisture content and then decreases. In contrast, the maximum dry unit weight and optimal moisture content correspond to the fitted curve's top, consistent with the dry density of fine-grained soil [27,28]. Wang et al [29,30] found that the dry density of gravelly calcareous sand increased with increasing water content when the water content was greater than 8%.…”
Section: Maximum Dry Density Experiments Of Round Gravel Soilsupporting
confidence: 64%
“…In addition, specific gravity of the natural clayey silt applied in this study is 2.55, and the plastic index is 29. Note that the natural clayey silt has been used in previous studies to explore undrained shear properties of hydrate-free and hydrate-bearing sediments [45,46]. Methane gas with a purity of 99.99% (Qingdao Ludong Gas Expert Co., Ltd., Qingdao, China) and distilled water are used to form noduled methane hydrate in light of a published method [47], and the nodules are stored in a liquid nitrogen container for future use.…”
Section: Experimental Apparatus and Materialsmentioning
confidence: 99%
“…The grain size ranges from ~1 µm to 200 µm, and the median grain size is 13.9 µm. For more information about physical properties of marine sediments, please refer to Wei et al [57]. Since methane hydrate formation within pores of fine-grained sediments is technically difficult and extremely time-consuming, tetrahydrofuran (THF) is selected as an analog of methane gas to form hydrate with pore water.…”
Section: Experimental Apparatus and Materialsmentioning
confidence: 99%
“…To simulate the real case in the Shenhu area of the South China Sea [64,65], values of the initial porosity of host sediments are controlled as 0.525, 0.500, and 0.482, corresponding to the initial void ratios of 1.105, 1.000, and 0.932. To avoid over-consolidation, values of the effective confining pressure are set as 1.0 MPa, 2.0 MPa, and 3.0 MPa based on the void ratio vs. the consolidation stress curve [57]. Values of hydrate saturation are selected as 0%, 30%, and 50%, corresponding to the THF vs. water mass ratios of 0, 0.060, and 0.104 [15].…”
Section: Test Designmentioning
confidence: 99%
See 1 more Smart Citation